Pollinators of Sikkim Mandarin Orange Citrus reticulata (Sapindales: Rutaceae) - Urbashi Pradhan; M. Soubadra Devy (Journal of Threatened Taxa, 2019)
Sikkim Mandarin Orange is a major cash crop of Sikkim with more than 12,000 farming families dependent upon it directly.  With increasing scientific records of positive contribution of pollinators in crop yield, an understanding of major pollinators of cash crops has become important.  In this paper, we present a comprehensive list of insect pollinators (24 species) for Sikkim Mandarin Orange.